2015
DOI: 10.1097/jom.0000000000000552
|View full text |Cite
|
Sign up to set email alerts
|

Heat Illness Among North Carolina Latino Farmworkers

Abstract: Objective Heat exposure is an important hazard for workers in manual occupations, including farmworkers. This analysis delineates the prevalence of heat illness among farmworkers, and the factors associated with heat illness. Methods North Carolina Latino male farmworkers completed interviews in August, 2013. They reported on heat exposure and behaviors over the previous 3 months while working both outdoors and indoors. Results A third (35.6%) of the participants reported heat illness while working outside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 22 publications
2
38
0
1
Order By: Relevance
“…For meta-analyses five and six, GRADE analysis revealed that the true effect is likely to be substantially different from the estimate of effect (very low confidence). Most (68%) 4,6,26,[33][34][35][39][40][41][42][43]45,46,[50][51][52][53][54][55]56,57, of the included studies incorporated low risk for selection bias, with the remaining studies presenting selection bias that was non-applicable (10%), 36, unclear (16%), 37,[47][48][49]118,[127][128][129][130][131][132] or, in some cases, high risk (6%) 5,38,44,133 due to acrossgroup variation in inclusion or exclusion criteria, and across-group differences in participant recruitment or selection. Most (61%) of the included studies incorporated low risk for confounding factors bias, with the remaining studies presenting confounding factor bias that was unclear (16%) 6 ,26,36,38,60,62,63,67,80,84,85,92,98-100,102,105,107-111,113,114,134-136 or high risk (23%) 33 ,35,37,44,45,47,49,59,66,74,83,86,89,91,94,96,118,127,128,132…”
Section: Resultsmentioning
confidence: 99%
“…For meta-analyses five and six, GRADE analysis revealed that the true effect is likely to be substantially different from the estimate of effect (very low confidence). Most (68%) 4,6,26,[33][34][35][39][40][41][42][43]45,46,[50][51][52][53][54][55]56,57, of the included studies incorporated low risk for selection bias, with the remaining studies presenting selection bias that was non-applicable (10%), 36, unclear (16%), 37,[47][48][49]118,[127][128][129][130][131][132] or, in some cases, high risk (6%) 5,38,44,133 due to acrossgroup variation in inclusion or exclusion criteria, and across-group differences in participant recruitment or selection. Most (61%) of the included studies incorporated low risk for confounding factors bias, with the remaining studies presenting confounding factor bias that was unclear (16%) 6 ,26,36,38,60,62,63,67,80,84,85,92,98-100,102,105,107-111,113,114,134-136 or high risk (23%) 33 ,35,37,44,45,47,49,59,66,74,83,86,89,91,94,96,118,127,128,132…”
Section: Resultsmentioning
confidence: 99%
“…5 Farmworkers are at an elevated risk for occupational injury and illness, including HRI, due to limited safety regulations, substandard housing conditions, long work hours, limited access to healthcare, social vulnerability due to guest-worker or immigration status, and working during peak summer heat. [6][7][8][9][10][11][12][13] Hired Latinx children constitute an especially vulnerable population within the larger farmworker community. 14,15 Findings from research with farmworkers and other outdoor workers are concerning, given the prognosis of higher global temperatures due to climate change.…”
Section: Heat-related Illness and Farmworkersmentioning
confidence: 99%
“…Research in North Carolina, Florida, Georgia, Oregon, and California has documented high prevalence of HRI and other heat-related conditions among farmworkers. 9,13,[17][18][19][20][21][22] In addition to the health risks of HRI, recent reviews observed increased occupational injury risk in high temperatures among young workers, male workers, and agricultural workers. 23,24 The percent of farmworkers who are women has increased substantially since 2001, [25][26][27] and research is documenting factors related to HRI among women workers.…”
Section: Heat-related Illness and Farmworkersmentioning
confidence: 99%
“…Nationwide, about a quarter of HRI deaths have been reported in the Agriculture, Forestry, Fishing, and Hunting industrial sector which comprises a significant portion of the economy in WA. Prior studies among agricultural workers have described a range of self‐reported prevalence of HRI symptoms, from 35% of workers reporting HRI in the previous 3 months in one study to 72% of workers reporting heat associated symptoms in the previous week 14,15 . The variable prevalence estimates of HRI symptoms can be partially attributed to multiple factors including differences in symptom recognition, HRI reporting, and varying levels of occupational and environmental exposures across sample populations.…”
Section: Introductionmentioning
confidence: 99%